Transcranial Brain Stimulation to Treat Aphasia: A Clinical Perspective - Fridriksson, Julius; Hubbard, H. Isabel; Hudspeth, Sarah Grace (Seminars in Speech and Language, 2012)
Transcranial brain stimulation was first introduced and described during mid-1900s. Since that time, the literature on brain stimulation has expanded with spurious advances in techniques and applications, from its use as a purely investigative tool used to better understand brain mechanisms to its use as a clinical treatment for neurologic diseases. This article offers a brief overview of the development, history, and mechanisms of transcranial brain stimulation, as well as an in-depth discussion of transcranial magnetic stimulation and transcranial direct current stimulation; two methods currently being investigated as treatments for aphasia. Our aim is to provide speech-language pathologists with an overview of the current state of literature on transcranial brain stimulation, as initial findings show it may be a promising new tool for aphasia rehabilitation.
Keywords: Brain stimulation; aphasia; treatment; transcranial magnetic stimulation; transcranial direct current stimulation